Estudo do encruamento dos aços AISI 304 e AISI 409 com uso da técnica de cisalhamento planar simples - Wellington Lopes (2009)
This research analyzed the effect of successive changes in the strain path of AISI 304 (type 304N) and AISI 409 stainless steel sheets on their work hardening behavior. Plastic deformation was imposed on these materials employing successive simple planar shear, tension or plane strain. These steels were chosen because of their contrasting work hardening behavior, associated with their crystalline structure. The AISI 409 steel has a BCC structure with profuse cross-slip and dynamic recovery, whereas the AISI 304 steel displays a low stacking fault FCC structure deforming with limited cross slip and dynamic recovery. Five types of strain paths were utilized: rolling/shearing, tension/shearing, forward/reverse shearing (Bauschinger type loading), rolling/tension/tension and rolling/tension/shearing. The direction of successive straining steps was varied so that varying values for the parameter, which indicates the severity of the strain path change, were obtained. Three types of testing specimens were employed, in order to allow the adequate successive deformation steps. The macroscopic results were analyzed through the true stress-true strain curves for the specimens along their processing path. In the case of the AISI 304 steel, further analyses involved X-rays diffraction and optical metallography, in order to study the observed strain induced phase transformations. The ductility of the materials was evaluated through their residual uniform elongation after processing. The results indicated that the structural characteristics of the stainless steels and the amount of strain were the main variables influencing the work hardening behavior of the materials It was also observed that the parameter was not able, by itself, to fully describe the importance of strain path changes in the two stainless steels presently under analysis, and that the initial state of the material and the deformation mode are of importance.